2004
DOI: 10.1007/s00210-003-0841-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endogenous endothelins in thermal and mechanical inflammatory hyperalgesia in mice

Abstract: Endothelin receptors have been involved in inflammatory, neuropathic and tumoral pain. In the case of inflammatory hyperalgesia, some previous papers have pointed towards the involvement of ETB receptors, although the stimulation of ETA receptors seems to participate in the development of the inflammatory reaction. We have studied the effect of ETA and ETB receptor antagonists in the thermal and mechanical hyperalgesia induced in a model of acute (induced by carrageenan) and chronic (induced by complete Freund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
0
51
0
2
Order By: Relevance
“…Apart from vasodilatory effect, endothelin antagonists also have the anti-inflammatory (Baamonde et al, 2004;Lehmberg et al, 2003;Bajory et al, 2002) and antioxidant activity (Andrasi et al, 2002). These properties of ET antagonist together may be contributing to its protective effect in the MCA occlusion model of acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from vasodilatory effect, endothelin antagonists also have the anti-inflammatory (Baamonde et al, 2004;Lehmberg et al, 2003;Bajory et al, 2002) and antioxidant activity (Andrasi et al, 2002). These properties of ET antagonist together may be contributing to its protective effect in the MCA occlusion model of acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that ET antagonists also possess anti-inflammatory property (Baamonde et al, 2004;Lehmberg et al, 2003;Bajory et al, 2002). Inflammation has been implicated as a secondary injury mechanism following ischemic stroke and a variety of experimental models and clinical studies have demonstrated the same.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, it has also been reported that the antinociception mediated by endothelin via the ET B receptor is opioid-sensitive (Khodorova et al, 2003). However, other investigators have reported that both ET A and ET B mediate nociception in abdominal writhing (Raffa et al, 1996) and carrageenan-induced mechanical hyperalgesia (Baamonde et al, 2004). These apparent discrepancies could be due to differences in experimental nociceptive models, the dose of endothelin, and time intervals of the nociceptive responses, which might detect the hyperalgesia of different sets of primary sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, concentrações menores (entre 10 pmols à ! alodinia mecânica (Balonov et al, 2006;Menendez et al, 2003;Piovezan et al, 1998 (Baamonde et al, 2004;Balonov et al, 2006), enquanto a dor evidente é inibida apenas pelo bloqueio do receptor ET A , da mesma forma que ocorre com todas as respostas pró-algésicas envolvendo ET 1 (Baamonde et al, 2004;Davar et al, 1998;De-Melo et al, 1998;;Gokin et al, 2001;Mckelvy et al, 2007;Mujenda et al, 2007;Raffa et al, 1996).…”
Section: Papel Das Endotelinas Na Dor E Inflamaçãounclassified
“…Khodorova et al (2006) (Baamonde et al, 2004;Davar et al, 1998;De-Melo et al, 1998;Gokin et al, 2001;Mckelvy et al, 2007;Mujenda et al, 2007;Raffa et al, 1996;).…”
mentioning
confidence: 99%